2007
DOI: 10.1007/s10750-006-0490-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fish and aquatic habitat complexity on amphibians

Abstract: Fish introductions are considered one of the most widespread anthropogenic threats to aquatic ecosystems. Their negative impact on native amphibian communities has received increasing attention in recent years. We investigated the relationship between the introduced fish, emergent vegetation cover and native amphibians in man-made ponds generated by regulation and dam building along the Tâ rnava Mare Valley (Romania) during the last 40 years. We inventoried amphibians and fish inhabiting 85 permanent ponds and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 48 publications
8
112
0
Order By: Relevance
“…However, the occurrence of reproduction and the relative abundance of tadpoles of the common toad was not affected by presence of the African clawed frogs. The common toad is resistant against some other alien species including predatory fish (Cruz et al 2006;Hartel et al 2007;Orizaola and Braña 2006). Moreover, the reproductive activity of the common toad in the study area occurs during the coldest months (December/February), when the activity of African clawed frogs is low due to low temperatures (Casterlin and Reynolds 1980;Measey 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence of reproduction and the relative abundance of tadpoles of the common toad was not affected by presence of the African clawed frogs. The common toad is resistant against some other alien species including predatory fish (Cruz et al 2006;Hartel et al 2007;Orizaola and Braña 2006). Moreover, the reproductive activity of the common toad in the study area occurs during the coldest months (December/February), when the activity of African clawed frogs is low due to low temperatures (Casterlin and Reynolds 1980;Measey 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The area studied by us allows proper conditions for these species and a large species richness since the permanent ponds are well represented and well vegetated [the mean amount of macrophyte vegetation cover of the ponds being up to 30% ], the ponds without predatory fish are still in high number [41% (Hartel et al 2007a)], the permanent ponds are closely situated to the forests [average distance is 232 m ], the forest coverage is large (Table I), and the land use is, in large part, traditional (Mountford & Akeroyd 2005). In this generally less-fragmented area, the dispersion of juveniles and a quick colonization of the newly created ponds is still possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relatively low values of the AUC for H. arborea and R. dalmatina in the pond occupancy-altitude relationship suggest that other variables have more influential effect than the pond altitude alone. Such variables are, for example, the reed cover of the ponds and the presence of predatory fish (Hartel et al 2007a), but in the case of H. arborea it may also be the light conditions (and implicit the temperature) of the ponds (Pellet & Hoehn 2004). The lack of pond occupancy-altitude relationship for other amphibian species that prefer permanent ponds such as T. cristatus (Gustafson et al 2006;Skei et al 2006) and B. bufo (Scribner ) may be explained by the larger ecological plasticity of these species in the altitudinal range and environmental conditions of this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Larzac, we mainly found goldfish to be present in ponds, but also pumpkinseed to a lesser extent (Supplementary Table 1; Denoël et al 2005a), whereas single cases of other species introductions have also been reported (Rondeau et al 2000). Pumpkinseeds are ferocious predators that can affect all aquatic life stages of amphibians (Parris et al 2001;Hartel et al 2007;Tomeček et al 2007;Bruslé and Quignard 2013). These fish are often present at high densities, forage in the varied aquatic microhabitats, and are also aggressive towards large amphibians such as frogs (Almeida et al 2014).…”
Section: Resistancementioning
confidence: 99%